The parasite - Evans, Richard Paul (Evans, Richard Paul. Michael Vey, 2022)
Michael and his friends have defeated Dr. Hatch and the Elgen, but they soon discover just how difficult it is to return to "normal" life. Taylor's prophetic visions take a dark turn when she begins dreaming of being locked in a cage surrounded by bats and a burning city, and Michael and his allies soon fear that like the legend of the Hydra, cutting off the head of Elgen only created new foes.